Opinions on Computer Audition for Bowel Sounds Analysis in Intestinal Obstruction: Opportunities and Challenges From a Clinical Point of View - Yang, Zhu; Huang, Luming; Jiang, Jingsun; Hu, Bing; Tang, Chengwei; Li, Jing (Frontiers in Medicine, 2021)
Intestinal obstruction (IO) is a common acute abdominal disease with abdominal pain, distension, vomiting, and constipation. It may need emergency surgery, since it possibly has high morbidity and mortality in cases of perforation, intestinal fistula, peritonitis, etc. At present, the diagnosis of IO has still depended on traditional bowel sounds(BS) auscultation, abdominal imaging examination (computerized tomography, X-ray). But in a certain situation, it is still difficult to identify the cause of IO, judge the severity and location of IO, and monitor the intestinal motility by those traditional methods. Computer audition, including machine learning and deep learning has greatly facilitated BS analysis. That might provide a new way to solve the above problems.